Factors influencing the acceptance of AI in innovating banking operations - a study from the perspective of Techcombank managers - Nguyen Phu Hung,; Ngo Thuy Duong,; Le Quynh Chi, (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
This research investigates manager attitudes toward AI-powered banking solutions through the lens of the Technology Acceptance Model (TAM). As AI technologies are increasingly used in the banking sector, understanding managers and workers’ acceptance and perception is critical for successful implementation and optimization of these systems. This study aims to identify the key factors influencing staff acceptance of AI tools, focusing on 4 primary factors, including: (i) Performance Expectation; (ii) Effort Expectation; (iii) Risk concerns; and (iv) Facilitating conditions. We found that the Performance Expectation, Effort Expectation, and Facilitating Conditions are factors that promote the AI acceptance while the Risk concerns do not. Code: 25052002